Risk spillovers between Bitcoin and ASEAN+6 Stock markets before and after COVID-19 outbreak: A comparative analysis with gold - Parichat Sinlapates; Tanit Sriwong; Surachai Chancharat (Journal of Risk and Financial Management, 2023)
This paper applies the multivariate GARCH models to investigate the role of Bitcoin as a hedge and safe haven for ASEAN+6 stock markets compared to gold. We used daily data for the dates 2 January 2017-20 January 2023, covering the recent COVID-19 pandemic. The empirical findings provide compelling evidence of cross-market shock and volatility transmission between stock returns and Bitcoin returns in both directions. Therefore, the dynamics of Bitcoin returns significantly influence the volatility of stock returns, and the relationship also holds in reverse. All diagonal element estimations are statistically significant for both periods, as shown by the findings of the return and volatility spillovers between the returns of gold and the ASEAN+6 stock market. For most ASEAN+6 equity markets evaluated, Bitcoin and gold are not safe havens, and their inclusion increases the portfolio downside risk.
Keywords: 650; Bitcoin; cryptocurrency; gold; spillover; volatility